Survey of Eye Toe Coordination and Dribbling Ability of Students at State Vocational School 4 Makassar - Misran; eko bagus fahrizqi; achmad karim (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2023)
This research is a type of descriptive research using the Surve research design. This study aims to see and know the description of the level of ankle coordination and ability to dribble in soccer games for students of SMK Negeri 4 Makassar. The population is all students of SMK Negeri 4 Makassar. The sample used was 20 people. The sampling technique is Simple Random Sampling. The data analysis technique used is descriptive analysis. The research results show that; 1) ankle coordination in students of SMK Negeri 4 Makassar is in the moderate category with a percentage of 40.00%. 2) The ability to dribble a football game for students at SMK Negeri 4 Makassar is in the moderate category with a percentage of 40.00%.